FOETOMATERNAL OUTCOME IN PATIENTS WITH OR WITHOUT PREMATURE RUPTURE OF MEMBRANES - Noor, Shehla; Fawwad, Ali; Shahzad, Hasan; Sultana, Ruqqia; Bashir, Rubina (Journal of Ayub Medical College Abbottabad, 2010)
Background: Preterm premature rupture of membranes is responsible for one third of all preterm births and is associated with significant maternal, foetal and neonatal risks. The objectives were to compare the foeto-maternal outcome in patient with and without preterm premature rupture of membranes. Method: This prospective comparative study was conducted in Gynae-C Unit of Ayub Teaching Hospital from Sep 2005 to Mar 2006. Total 170 cases were recruited in the study, out of which 85 had Preterm Premature Rupture of Membranes (PPROM), and 85 had preterm labour without PROM. Patients' data were recorded on a performa. Maternal outcome was measured on the basis of presence of fever and mode of delivery. Foetal outcome was measured on the basis of weight of the baby, and presence of infection (fever), APGAR score and neonatal death. Analysis was performed using SPSS- 10. Results: The primary data arranged in groups was divided into PPROM and no-PPROM groups. The PPROM was found to be frequent in younger age group between 15-25 years while no-PPROM was common among the age group between 26-35 years (p=0.002). Lower socioeconomic class and history of previous one or more preterm delivery was significantly associated with PPROM (p=0.001). Maternal fever was also significant in the PPROM group (p=0.01). Low birth weight was statistically significant in the PPROM group. Majority of the babies born to mother were either extremely low birth weight or low birth weight, i.e., between 1-25 kg p-value 0.005. Low APGAR score at the time of delivery (p=0.01) and foetal infection (p=0.002) between the PROM and no-PPROM group was found to be statistically significant Neo-natal deaths was also higher in the PPROM group as compared to no PPROM group (11 verses 2) (p=0.009). Conclusion: In our study premature rupture of membrane had increased neonatal morbidity and mortality as compared to preterm birth. Strategies should be developed for its prevention. Keywords: Preterm Premature rupture of membranes, PPROM, Preterm birth